KARAKTERISTIK KIMIA YOGHURT SINBIOTIK DENGAN PENAMBAHAN TEPUNG HANJELI (Coix lacryma-jobi L.): CHEMICAL CHARACTERISTICS OF SYNBIOTIC YOGURT WITH THE ADDITION OF HANJELI FLOUR (Coix lacryma-jobi L.) - Dewiarum Sari; Sari Wiji Utami (Tropical Animal Science, 2026)
Synbiotic yogurt is yogurt made by combining probiotics and prebiotics that can increase functional value because they have a positive impact on health. Commercial starter "biokul" contains Lactobacillus acidophilus and Bifidobacterium, which are groups of probiotic bacteria that can live in the intestine. hanjeli flour (Coix lacryma-jobi L.) contains bioactive compounds that can be used as a substrate for probiotic growth, in addition to being able to improve the chemical quality of synbiotic yogurt. This study aims to determine the chemical characteristics of synbiotic yogurt with the addition of hanjeli flour (Coix lacryma-jobi L.) as a natural stabilizer. The research parameters include protein content, fat content, and water content. The method used in this study was a Completely Randomized Design (CRD) consisting of 4 treatments, including P0 (without the addition of 0% hanjeli flour); P1 (addition of 1% hanjeli flour); P2 (addition of 2% hanjeli flour); and P3 (addition of 3% hanjeli flour). The data obtained were analyzed using Analysis of Variance (ANOVA); if there was a significant difference, then continued with Duncan's Multiple Range Test (DMRT). The results of the analysis of variance showed that the difference in the concentration of millet flour had a significant effect (P <0.05) on the protein content, fat content, and water content of synbiotic yoghurt. The best treatment from this study was obtained in treatment P3 (addition of 3% millet flour), which had a protein content of 3.41%, a fat content of 2.72%, and a water content of 82.79%.